Determination of Metal Loading in Heterogeneous Catalyst by Slurry Sampling Flame Atomic Absorption Spectrometry - Garcia,Marco A. S. (2015)
Quantification of metal loading in supported catalysts is imperative; however, the analytical methods are usually time-consuming, expensive, and require sophisticated equipment and sample extraction with hazardous and corrosive strong acids. Herein, we report a new method for quantification of metal in supported catalysts using slurry sampling flame atomic absorption spectrometry. The slurry sampling method was used for determination of gold and the results were similar to those obtained with the traditional extraction method using aqua regia; however, it overcomes the main drawbacks associated with sample digestion by avoiding the use of concentrated toxic reagents, minimizing sample manipulation, and consequently, reducing the risks of contamination and the sample preparation time. Ultrasound radiation optimization associated with the solvent, mass of sample, concentration, and matrix effect in the slurry analysis allowed direct analysis by using the calibration in aqueous medium. The slurry sampling procedure could be applied to other catalysts with different supports and in bimetallic systems.